2020
DOI: 10.1093/toxsci/kfaa017
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Human Relevance of the Liver Tumors Observed in Female Mice Treated With Permethrin Based on Mode of Action

Abstract: In 2-year studies, the nongenotoxic pyrethroid insecticide permethrin produced hepatocellular tumors in CD-1 mice but not in Wistar rats. Recently, we demonstrated that the mode of action (MOA) for mouse liver tumor formation by permethrin involves activation of the peroxisome proliferator-activated receptor alpha (PPARα), resulting in a mitogenic effect. In the present study, the effects of permethrin and 2 major permethrin metabolites, namely 3-phenoxybenzoic acid and trans-dichlorochrysanthemic acid, on cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…In a study in marmosets, the PPARa activator clofibrate was shown not to produce liver tumors after 6.5 years of treatment, although this is less than the expected life-span of this species (Corton et al 2018). Several studies have demonstrated that rodent PPARa activators do not stimulate RDS in cultured human hepatocytes (Lake 2009;Corton et al 2014Corton et al , 2018Kondo et al 2020). In vivo studies with chimeric mice with human hepatocytes have demonstrated that the PPARa activator fenofibrate does not increase RDS in human hepatocytes and results in downregulation of pathways related to DNA synthesis (Tateno et al 2015;de la Rosa Rodriguez et al 2018) similar to the results with CAR activators in chimeric mice with human hepatocytes.…”
Section: Comparison Of the Hepatic Effects Of Car Pxr And Ppara Activatorsmentioning
confidence: 98%
See 2 more Smart Citations
“…In a study in marmosets, the PPARa activator clofibrate was shown not to produce liver tumors after 6.5 years of treatment, although this is less than the expected life-span of this species (Corton et al 2018). Several studies have demonstrated that rodent PPARa activators do not stimulate RDS in cultured human hepatocytes (Lake 2009;Corton et al 2014Corton et al , 2018Kondo et al 2020). In vivo studies with chimeric mice with human hepatocytes have demonstrated that the PPARa activator fenofibrate does not increase RDS in human hepatocytes and results in downregulation of pathways related to DNA synthesis (Tateno et al 2015;de la Rosa Rodriguez et al 2018) similar to the results with CAR activators in chimeric mice with human hepatocytes.…”
Section: Comparison Of the Hepatic Effects Of Car Pxr And Ppara Activatorsmentioning
confidence: 98%
“…cytotoxicity, CYP enzyme induction, and RDS studies) as they can maintain functional activities for at least 24-72 h. Such cultures permit the medium-throughput screening of compounds and are thus useful for examining inter-species and inter-individual differences. While PB has been shown to stimulate RDS in cultured mouse and rat hepatocytes, many studies from a number of different laboratories have demonstrated that PB does not increase RDS in cultured human hepatocytes (Parzefall et al 1991;Hirose et al 2009;Yamada et al 2015;Okuda et al 2017a;Haines et al 2018b;Peffer et al 2018a;Wiemann et al 2019;Kondo et al 2020;Lake et al 2020;Strupp et al 2020). For example, in both published (Hirose et al 2009;Yamada et al 2015;Okuda et al 2017a;Kondo et al 2020) studies (five male and nine female donors), and unpublished studies (six male and three female donors) from our laboratory, overall PB was shown not to increase hepatocyte RDS in cultured primary human hepatocytes from a total of 23 human donors (11 males and 12 females) with ages ranging from 10 months to 80 years.…”
Section: Studies In Cultured Human Hepatocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, primary cultures of animal and human primary hepatocytes have been extensively used for in vitro testing (e.g., cytotoxicity, CYP enzyme induction, and RDS studies) as they can maintain functional activities for at least 24-72 h 6 . While PB has been shown to stimulate RDS in cultured mouse and rat hepatocytes, many studies from different laboratories have demonstrated that PB does not increase RDS in cultured human hepatocytes 20,[65][66][67][69][70][71][72][73][74] 84 .…”
Section: Studies In Cultured Human Hepatocytesmentioning
confidence: 99%
“…Small molecule inhibitors have been used to control cellular protein levels through occupancy-driven pharmacology as the mode of action. However, this strategy only temporarily inhibits the functions of regulatory proteins 50 , 51 . Finding new models is essential to control cellular protein levels.…”
Section: Targeted Protein Degradation As a Promising Strategy For Drumentioning
confidence: 99%